Տավուշի ջրամբարի էկոլոգիական վիճակի գնահատումը - Մկրտչյան, Անժելա; Երիցյան, Լուսինե (ՀԱԱՀ հիմնադրամ)
Изучено экологическое состояние Тавушского водохранилища, химический состав воды, загрязненность тяжелыми металлами и нитратами. Определена пригодность воды для орошения. Согласно данным исследований, содержание меди в водохранилище в марте и июне составляло 0.085 и 0.094 мг/л, цинка – 0.801 и 0.814 мг/л, свинца – 0.03 и 0.05 мг/л, нитратов – 9.5 и 11.4 мг/л. По экологическим нормам содержание меди и свинца оценено как недостаточное (4-й класс), цинка и нитратов – плохое (5-й класс), что вызывает беспокойство, поскольку такую воду нельзя использовать для ирригационных целей. The studies were dedicated to the ecological condition of the Tavush reservoir. The chemical composition, heavy metals and nitrates pollution of the reservoir water was investigated. The goal was to find out the suitability of the water for irrigation. The research revealed that based on the irrigation coefficient evaluated by the content of Na+ and Cl- ions, water in the Tavush Reservoir is considered sufficiently suitable. According to the Sodium Adsorption Ratio (SAR) determined by the ratio of Ca2+, Mg2+, and Na+ ions, the water also seems to comply with the required criteria. However, the level of risk posed by the Mg2+ ion content, calculated from the ratio of Mg2+ and Ca2+ ions, presents some risk to the soil. The water’s pH is slightly alkaline (pH 7.8), which is due to the presence of Ca, Mg, and K ions, though their quantities do not exceed permissible limits. The dissolved salts make up 0.056 %, which is fully permissible for irrigation purposes. No CO32- ions have been detected. It was also found out that in March and June, the copper concentrations in the water were 0.085 mg/L and 0.094 mg/L, zinc was 0.801 mg/L and 0.814 mg/L, and lead was 0.03 mg/L and 0.05 mg/L, while the nitrate content was 9.5 mg/L and 11.4 mg/L, respectively. According to these data, the water quality in June is rated as “poor” (5th class) due to the high levels of zinc and nitrate ions. This is a serious cause for concern, since such water can not be considered as suitable for irrigation purposes.
Keywords: Ագրոէկոլոգիա